Exchange rate regimes and economic performances in Sub-Saharan Africa - (:unkn) unknown (My University, 2014)
In this PhD. thesis titled “Exchange Rate Regimes and Economic Performances in Sub-Saharan Africa”, we carried out analysis to show the relationship between the choice of exchange rate regimes and economic performances in Sub-Saharan Africa (SSA). In order to proceed to comparative analysis, first we breakdown the global sample (SSA) into two, which are the monetary union countries or CFA franc zone countries (ZCFA) and the non-monetary union countries or countries outside CFA franc zone (HZCFA), then we breakdown the sample into four subsample, which are the West Africa Economic and Monetary Union (WAEMU) countries, the Central Africa Economic and Monetary Community (CAEMC) countries, the HZCFA countries with fixed exchange rate regimes and the HZCFA countries with flexible exchange rate regimes. Our analysis focuses on the following topics:1. Exchange rate regimes and monetary policies in SSA2. Convergence between WAEMU and CAEMC3. Exchange rate regimes and macroeconomic instabilities in SSA4. Exchange rate regimes, Real exchange rate and its adjustment in SSA5. Exchange rate regimes, macroeconomic instabilities and economic growth in SSAThe empirical results based on topics mentioned above conducted to mixed results depending on our subsamples. Also, they show that the exchange rate regimes have not been well managed in SSA, and that they have been sometimes used as means to hide bad economic results induced by non-effective economic policies and non-effective economic decisions.
Keywords: African Research